An online survey on coping methods for genitourinary syndrome of menopause, including vulvovaginal atrophy, among Japanese women and their satisfaction levels - Hiroaki Ohta; Mariko Hatta; Kuniaki Ota; Remi Yoshikata; Stefano Salvatore (BMC, 2023)
Abstract Background This study aimed to explore the current situation and existing issues regarding the management of vulvovaginal atrophy (VVA) or the genitourinary syndrome of menopause (GSM). A nationwide web-based questionnaire survey was conducted among 1,031 Japanese women aged 40 years or older. Materials and methods Eligible women were asked to complete a questionnaire about how they dealt with their symptoms and how satisfied they were with their coping methods. Results Of those highly conscious of their GSM symptoms (n = 208; 20.2%), 158 had sought medical consultation (15.3%), with only 15 currently continuing to seek consultation (11.5%). Of the specialties consulted, gynecology was the most frequently consulted (55%). Furthermore, those unwilling to seek medical consultation despite their symptoms accounted for the greatest proportion (n = 359; 34.8%), with 42 (23.9%) having never sought consultation. Topical agents, e.g., steroid hormone ointments/creams, were the most frequent treatments provided by the clinics (n = 71; 40.3%), followed by oral and vaginal estrogens (n = 27; 15.5%), suggesting that estrogen therapy was not the first choice of treatment at the clinics. While 65% of patients treated at the clinics reported satisfaction with the treatments, this was inconsistent with the fact that many were reported to have remained untreated and very few continued with treatment. Conclusions Survey results suggest that GSM, including VVA, remains underdiagnosed and undertreated in Japan. Medical professionals should deepen their understanding of GSM and raise their level of care to select the appropriate treatment for the condition.